Basic Framework of Regional Model for Disaster Waste Estimation and Distribution by Using Spatial Approach in Central Java-Indonesia. (November 2019) - Maryono, M; Seruningtyas, K; Roynaldi, A D; Sudarno,; Hadiyanto,
Abstract: Disaster are becoming more frequent around the world and more intense in urban areas. Central Java is the province with the largest number of disasters in Indonesia. Disaster create amount of disaster waste and sometime very huge, many times comparing to daily municipal waste generation. Government and local citizen sometimes are unable to handling disaster waste. Since effective implementation of disaster waste management (DWM) will lead quick and better recovery of living and avoid more environmental risk, high level regional government such as provincial should help. To make effective support, it is important that provincial government develop a model to monitor disaster waste generation in each regency and cities. This study aims to develop basic framework of regional model for disaster waste estimation and distribution in provincial level. This study used Central Java Province as a case study. To estimate disaster waste in Central Java, this study developed an index system as a basic model. It is about basic comparison of disaster waste generation in all central java regencies or cities. Disaster waste is associated with total disaster events. This study utilized GIS tools to express model and system. This study developed of regional model disaster waste estimation in Central Java, divided by 3 sub decades. Study result shown that in first decade 1990-1999 the highest index of disaster waste estimation is Brebes Regency. Second decade 2000-2009 the highest index of disaster waste estimation is Semarang Regency and the third decade 2010-2018 the highest index of disaster waste estimation in Cilacap Regency.